Deblurring images matrices, spectra, and filtering - Hansen, Per Christian 1957-; Nagy, James G.; O'Leary, Dianne (Society for Industrial and Applied Mathematics (SIAM, 3600 Market Street, Floor 6, Philadelphia, PA 19104), 2006)
Describes the deblurring algorithms and techniques collectively known as spectral filtering methods, in which the singular value decomposition, or a similar decomposition with spectral properties, is used to introduce the necessary regularization or filtering in the reconstructed image. The concise MATLAB implementations described in the book provide a template of techniques that can be used to restore blurred images from many applications
Keywords: Mathematisches Modell; Image processing / Mathematical models; Bildverarbeitung; Mathematische Methode; Bildschärfe